Covid-19 is impact to air quality transformation based on Landsat: a case from Makassar City, Indonesia. Issue 1 (June 2021) - Muhtar, G A; Mariati, H; Ridwan,; Hasanuddin,; Sandi, R; Okviyani, N
Abstract: Makassar is city center in Eastern Indonesia, so that many sectors such as industry, services, settlements, education, trade, and transportation are developing rapidly. These various activities produce exhaust emissions, such as SO 2 (Sulfur Dioxide) and NOx (Nitrogen Oxide), which can be bad for health. Landsat is a measuring tool used to monitor air quality in a large area. The research objective was to measure changes in SO 2 and NOx using Landsat 8 OLI in Makassar City before covid (October 2019) and during covid (during PSBB/June 2020 and after PSBB/October 2020). Kruskal Test is used to analyze transformation difference significantly on SO 2 and NOx before the covid pandemic and during a covid pandemic. The result shows that SO 2 is higher before covid. That is 220 ppm in October 2019. While covid, it is 42 ppm on June 2020 and 98 ppm on October 2020. The same thing happened to NOx. NOx is higher before covid that is 177 μ/m 3 . But while covid, it is decreased. That is 173 μ/m 3 in June 2020 and 175 μ/m 3 in October 2020. Kruskal Test shows a significant difference between SO 2 and NOx before and during a covid pandemic.